Laparoscopic excision of large omental cyst at department of pediatric surgery in Sanglah general hospital, Bali, Indonesia - Oka Kasuma Dewi, A. A. A.; Ariyanta, Kadek Deddy (International Journal of Research in Medical Sciences, 2019)
Omental cyst is rare. All conditions most likely being of congenital or benign neoplastic lymphatic origin. Patients with Omental cysts usually present with abdominal distention and a painless abdominal mass. The most common physical finding of an omental cyst is a freely movable abdominal mass. The diagnostic procedure include CT scans. Complete excision by open or laparoscopically of the cysts is considered as the treatment of choice. Recurrence and malignant deterioration of omental cysts are rare. A case report of a large omental cyst which had been laparoscopically-treated using morcellator. Laparoscopic morcellation is a technique used in gynecological surgeries such as hysterectomy and myomectomy to remove uteri and uterine fibroids (leiomyomas) through a small abdominal incision. Authors present a case of 3 year old female with pre-operative assessment tumor intra-abdominal suspect abdominal cyst. Subsequently, laparoscopic resection of omental cyst with morcellator was performed. The histopathological report was omental cyst. Omental cysts are rare, but can be shown to have atypical abdominal symptoms and radiologic findings, so clinicians must keep in mind that omental cysts causing abdominal symptoms can be misdiagnosed as simple ovarian cysts of inflammation. Omental cysts can be removed safety laparoscopically with morcellator without bowel or vessel injury.